Growing Sequence Effects of Core-shell Nanostructure on Morphology and Electrocapacitive Ability for Energy-Storage Electrodes. (20th November 2017) - Hong, Wei-Lun; Lin, Lu-Yin; Lin, Lu-Ying
Graphical abstract: Highlights: Growing sequence effects on the morphology and electrode performance are studied. Nix Coy O nanowire@Nix Moy O nanosheet and Nix Coy O nanosheet@MnO2 nanosheet are made. Forming core-shell structures depends on size and intrinsic property of materials. Growth mechanism for the core-shell nanostructures is proposed. A specific capacitance of 4.26 F/cm 2 is got for the Nix Coy O@Nix Moy O electrode. Abstract: Synthesizing the core-shell structure of metal oxides as the electrocapacitive material is one of the feasible ways to fabricate effective energy storage electrodes. Based on the same materials for constructing the core-shell structure, effects of the material exchange in the inner and outer positoins on the morphology and the electrochemical performance are primarily investigated in this study to understand the core-shell structure in a novel way. Two couples of the materials are used on constructing the double-component structures, i.e., the nickel cobalt oxide (Nix Coy O) nanowires and nickel molybdenum oxide (Nix Moy O) nanosheets as well as the Nix Coy O nanosheets and MnO2 nanosheets. The well-defined core-shell structures are obtained when Nix Coy O is used as the core, regardless of the morphology of Nix Coy O and the shell materials. However, the pure nanosheet or nanowire arrays are obtained when Nix Coy O are acted as the shell. It is inferred that the formation of the core-shell structure significantly depends on the size and the intrinsic properties of the core and the shell, and the material having the larger size should grow in the inner position to synthesize the well-defined core-shell structure. Better electrochemical performances are achieved for the double-component electrodes no matter the morphology is single-structure or core-shell type, as compared with those for the single-component electrodes. Also, among the double-component electrodes those composed of well-defined core-shell structures show better electrochemical performances, probably due to the larger active surface area for conducting the Faradic reactions. The highest specific capacitance (CF ) of 4.26 F/cm 2 is achieved at the current density of 5 mA/cm 2 for the Nix Coy O@Nix Moy O core-shell electrode.